2016
DOI: 10.1590/1806-9061-2016-0324
|View full text |Cite
|
Sign up to set email alerts
|

Carcass Traits and Immune Response of Broiler Chickens Fed Dietary L-Carnitine, Coenzyme Q10 and Ractopamine

Abstract: This study was conducted to evaluate the effects of coenzyme Q 10 , L-carnitine and ractopamine supplementation, alone and in combinations, on carcass traits and immune response of broiler chickens. Five hundred and twelve one-day-old Ross 308 male broiler chickens were randomly allocated into eight treatments with four replicates each. A 2×2×2 factorial arrangement was applied, with two levels of coenzyme Q 10 (0 and 40 mg/kg), two levels of L-carnitine (0 and 200 mg/kg) and two levels of ractopamine (0 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…The results of this study are in agreement with Nemati et al [13] and Asadi et al [14], who reported that coQ10 supplementation of hatched chickens diets at different ages were high responders for antibody production of ND, AI, and IBD compared to the negative and positive control groups. However, the degree of response for immune system (humoral and cell mediated immune systems) to in ovo injection depends upon genetics, parent stock age, egg size, and incubation conditions [8].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results of this study are in agreement with Nemati et al [13] and Asadi et al [14], who reported that coQ10 supplementation of hatched chickens diets at different ages were high responders for antibody production of ND, AI, and IBD compared to the negative and positive control groups. However, the degree of response for immune system (humoral and cell mediated immune systems) to in ovo injection depends upon genetics, parent stock age, egg size, and incubation conditions [8].…”
Section: Discussionsupporting
confidence: 93%
“…Though it seems that the difference in hatchability percentage has been observed between the two control groups (the sham and uninjected groups) related to the effect of injection on egg fertility and hatching performance. Higher improvements in immunity system with regard to higher antibody production by in ovo injection of coQ10 in present study are in accordance with the results of many studies [13, 14, 31]. It is due to special effect of antioxidant components that protects tissue of immunological organs against destruction [38], also influences of coQ10 on helper T-cells, phagocytosis activity, and prostaglandin synthesis in lymphoid organelles [8, 13].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The feed was withdrawn three hours before slaughter (Asadi et al, 2016). At the end of the trial (42 days old), two birds per each replica, whose body weights were nearest to the average body weight of their groups, were selected from every treatment (12 in treatment, 48 birds in total).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, L-carnitine can be effective in improving immunity, increasing resistance to diseases and decreasing ascites in broiler chickens. Positive effect on the immune system 200 mg/kg Asadi et al, 2016 No effect on antibody titers against Newcastle disease and bronchitis 100 mg/kg Azadmanesh and Jahanian, 2014 No effect on the production of antibodies against SRBC 100, 200 mg/kg Kheirkhah et al, 2009 Increase in antibody titers against SRBC and Newcastle disease. Weight gain of thymus, spleen, and bursa of Fabricius 100 mg/kg Golzaradabi et al, 2011 Increased thymus weight, increased antibody level against SRBC 1000 mg/kg Deng et al, 2006 Effect of L-carnitine on blood parameters of broiler chickens Xu et al (2003) showed that the application of (0, 25, 50, 75 and 100 mg/kg) L-carnitine, especially 50 mg/kg, reduced serum triglyceride in broiler chickens.…”
Section: Effect Of L-carnitine On the Immunity Of Broiler Chickensmentioning
confidence: 99%